Activation of NO-cGMP Signaling Rescues Age-Related Memory Impairment in Crickets - Matsumoto, Yukihisa; Matsumoto, Chihiro S.; Takahashi, Toshihumi; Mizunami, Makoto (Frontiers in Behavioral Neuroscience, 2016)
Age-related memory impairment (AMI) is a common feature and a debilitating phenotype of brain aging in many animals. However, the molecular mechanisms underlying AMI are still largely unknown. The cricket Gryllus bimaculatus is a useful experimental animal for studying age-related changes in learning and memory capability because the cricket has relatively short life-cycle and a high capability of olfactory learning and memory. Moreover, the molecular mechanisms underlying memory formation in crickets have been examined in detail. In the present study, we trained male crickets of different ages by multiple-trial olfactory conditioning to determine whether AMI occurs in crickets. Crickets three weeks after the final molt (three-week-old crickets) exhibited levels of retention similar to those of 1-week-old crickets at 30 min or 2 hr after training, but they showed significantly decreased levels of 1-day retention, indicating AMI in long-term memory (LTM) but not in anesthesia-resistant memory (ARM) in olfactory learning of crickets. Furthermore, 3-week-old crickets injected with a nitric oxide (NO) donor, a cyclic GMP (cGMP) analogue or a cyclic AMP (cAMP) analogue into the hemolymph before conditioning exhibited a normal level of LTM, the same level as that in 1-week-old crickets. The rescue effect by NO donor or cGMP analogue injection was absent when the crickets were injected after the conditioning. For the first time, an NO donor and a cGMP analogue were found to antagonize the age-related impairment of LTM formation, suggesting that deterioration of NO synthase (NOS) or molecules upstream of NOS activation is involved in brain aging processes.